Hypercoagulation and Antithrombotic Treatment in Coronavirus 2019: A New Challenge - Violi, Francesco; Pastori, Daniele; Cangemi, Roberto; Pignatelli, Pasquale; Loffredo, Lorenzo (Thrombosis and haemostasis, 2020)
Abstract The novel coronavirus 2019 (COVID-19) is clinically characterized by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is responsible for a high number of patients needing mechanical ventilation or intensive care units treatment and for the elevated mortality risk. A link between COVID-19 and multiorgan failure may be dependent on the fact that most COVID-19 patients are complicated by pneumonia, which is known to be associated with early changes of clotting and platelet activation and artery dysfunction; these changes may implicate in thrombotic-related events such as myocardial infarction and ischemic stroke. Recent data showed that myocardial injury compatible with coronary ischemia may be detectable in SARS-CoV-2 patients and laboratory data exploring clotting system suggest the presence of a hypercoagulation state. Thus, we performed a systematic review of COVID-19 literature reporting measures of clotting activation to assess if changes are detectable in this setting and their relationship with clinical severity. Furthermore, we discussed the biologic plausibility of the thrombotic risk in SARS-CoV-2 and the potential use of an antithrombotic treatment.